A música no segundo Nietzsche - Santos, Felipe Thiago dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Human, All Too Human (1878) represents the beginning of the phase in which the Nietzsche philosophy (1844 - 1900) breaks up with their former and major influences: Schopenhauer and, mostly Wagner. Regarding to the art, this destructive time of Nietzsche's philosophy becomes to criticize the musician (genius) deification and the music concept as an ineffable language (expression of the world essence) and / or feelings, ideas that were developed by Romanticism especially by the Richard Wagner composer. Moreover, Nietzsche also criticizes - with some exceptions - another concept present at the time that intends to show the music listening criteria are solely sound relations (formalism), conception defended by Viennese music critic Eduard Hanslick in From Belo Musical (1851). However, the second phase of Nietzschean thought (between 1876- 1882) conceives art not only in a negative way. In the second Nietzsche we can see from a historical musical defended by him in which music, uprooted of misinterpretations about its effects and contents can support life while an affirming experience. Therefore, first of all our goal will be to expose, from Nietzsche criticism presents in its second phase to the design of music present in his time, a music philosophy with own characteristics. Secondly, we will show that even in its second phase, this philosophy uses music to point out a singular experience, such as man affirmation against the world. For the enjoyment of our goals, we will analyze both works of the second phase of Nietzsche as posthumous unpublished in addition to dialogue with Brazilian and foreign commentators.

Humano, Demasiado Humano (1878) representa o início da fase em que a filosofia de Nietzsche (1844 - 1900) rompe com suas antigas e principais influências: Schopenhauer e, sobretudo, Wagner. No que tange à arte, esse momento destrutivo da filosofia de Nietzsche passa a criticar a deificação do músico (gênio) e a concepção de música enquanto linguagem do inefável (expressão da essência do mundo) e/ou dos sentimentos, ideias essas desenvolvidas pelo Romantismo e, sobretudo, pelo compositor Richard Wagner. Além disso, Nietzsche também critica - com certa ressalva - outra concepção presente na época, a saber, a que pretende mostrar que o critério da audição musical são, unicamente, as relações sonoras (formalismo), concepção defendida pelo crítico musical vienense Eduard Hanslick em Do Belo Musical (1851). Mas a segunda fase do pensamento nietzschiano (compreendida entre 1876 e 1882) não concebe a arte apenas de uma maneira negativa. No segundo Nietzsche podemos perceber, a partir de uma historicidade musical defendida pelo filósofo que, a música, desarraigada de falsas interpretações acerca dos seus efeitos e do seu conteúdo, pode fundamentar a vida enquanto uma experiência afirmadora. Portanto, nosso objetivo será o de expor, a partir das críticas de Nietzsche em sua segunda fase à concepção de música presentes em sua época, uma filosofia da música de características próprias. Num segundo momento mostraremos que, mesmo em sua segunda fase, essa filosofia se utiliza da música para apontar uma experiência singular, isto é, de afirmação do homem frente ao mundo.
Keywords: Nietzsche, Friedrich Wilhelm 1844-1900; Filosofia alemã; Música e filosofia; Music and philosophy